Evaluating the psychometric properties of a Malay version of Bostick's (1992) library anxiety scale - Karim, N.H.A.; Noor Rashidalila, A.R. (2014)
The purpose of this study was to identify the components of library anxiety using a Malay version of Bostick's (1992) Library Anxiety Scale (LAS) and to examine the effects of demographic variable such as gender, native language, year of study, prior exposure to library services and medium of instruction at school on the variation in the library anxiety construct. A 46-item Malay version of Bostick's (1992) Library Anxiety Scale (LAS) was tested among 130 medical students drawn randomly from a population of 423 students pursuing their Bachelor of Medicine, Bachelor of Surgery (MBBS) Degree. The findings revealed a 3-factor solution which corresponded to the five factors as found by Bostick's (1992) pioneering psychometric effort of library anxiety. The subscales of library anxiety were named as barriers with staff, affective barriers and comfort with library technology. The factor 'barriers with staff 'explained 19.76% of the variance in the library construct. The second factor 'affective barriers' explained 11.55% of the variance in the library construct. The third factor 'comfort with library technology' explained 10.282% of the variance in the library construct. The overall scale as well as each of three sub-scales was submitted to an internal reliability assessment using Cronbach's internal reliability coefficient alpha. All three subscales were found to have satisfied the 0.70 criterion as recommended by Nunnally and Bernstein (1994). Despite the fewer number of sub-scales that were yielded by the Malay version of Bostick's (1992) Library Anxiety Scale (LAS), the translated scale has been shown to be a valid and reliable instrument.